2017
DOI: 10.1111/sltb.12333
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Exposure in the Population: Perceptions of Impact and Closeness

Abstract: Recent studies of people exposed to suicide point to a continuum of effects moderated by a perception of closeness to the deceased. We investigated the importance of perception of impact of the death on mental health outcomes of those exposed to suicide. Female sex, younger age, and multiple exposures to suicide were associated with greater risk for poorer outcomes. Suicide exposed with high impact was more likely to have depression, anxiety, posttraumatic stress disorder, prolonged grief, and suicide ideation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 11 publications
4
60
1
2
Order By: Relevance
“…Given the relatively high frequency of familial exposure to suicidal behaviour in both (ideation and attempt) groups of prisoners, it is important not to dismiss the association between exposure and suicide risk entirely. Indeed, research should look beyond the crude frequencies of suicidal behaviour that one is exposed to, and shift its focus to different aspects of exposure (e.g., perceived impact and closeness to the decedent; Cerel et al, 2017) which may explain why some prisoners who experience suicidal ideation are propelled towards suicide, whereas others are not.…”
Section: Discussionmentioning
confidence: 99%
“…Given the relatively high frequency of familial exposure to suicidal behaviour in both (ideation and attempt) groups of prisoners, it is important not to dismiss the association between exposure and suicide risk entirely. Indeed, research should look beyond the crude frequencies of suicidal behaviour that one is exposed to, and shift its focus to different aspects of exposure (e.g., perceived impact and closeness to the decedent; Cerel et al, 2017) which may explain why some prisoners who experience suicidal ideation are propelled towards suicide, whereas others are not.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that 31.79% had lost someone close to them to suicide, and this is in keeping with the data that a third of FIGURE 2 | Is social media a good platform for people to ask for help and seek support from others? Americans know someone who has died of suicide (39). We did not explore how the closeness impacted them.…”
Section: Discussionmentioning
confidence: 99%
“…Staff should be trained to view any deficits in performance in the context of the impacts described here, set deadlines considerately, and familiarise themselves with bereavement support services. Restrictive compassionate leave policies should take into account our findings, and evidence that perceptions of closeness to the deceased predict the likelihood of developing depression or anxiety after the loss [ 40 , 41 ]. These present a rationale for widening such rigid eligibility.…”
Section: Discussionmentioning
confidence: 99%